From Pixels to Sentence: A Comprehensive Study of Transformers-Based Models for Image Captioning - Haider Jaber Samawi; Ayad Rodhan Abbas (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2026)
The task of image captioning, which involves generating descriptive textual content from visual input, is a pivotal challenge in multimodal learning. This research delves into the advancements in image captioning facilitated by Transformer-based models, comparing their performance, architectures, and innovations across various tasks. Traditional models, such as CNNs paired with RNNs, were initially used to extract visual features and generate corresponding captions. However, the introduction of Transformer architectures has significantly enhanced the performance of image captioning systems, allowing for more coherent, context-aware, and grammatically correct captions. This paper explores the evolution of Transformer-based models, with a particular focus on the Encoder-Decoder, Vision-Language Fusion, and End-to-End Transformers models. By analyzing state-of-the-art architectures such as ViT, GPT, BLIP, and CoCa, the study demonstrates how these models address long-range dependencies, utilize self-attention mechanisms, and seamlessly integrate vision and language for improved caption generation. Furthermore, the paper evaluates the strengths, challenges, and limitations of these approaches, including issues related to computational complexity, dataset biases, and caption diversity. Ultimately, this study presents a comprehensive comparison of these models, offering insights into future research directions in the field of image captioning.